Diversity and dynamics of the Drosophila transcriptome - Brown, James B.; Boley, Nathan; Eisman, Robert; May, Gemma E.; Stoiber, Marcus H.; Duff, Michael O.; Booth, Ben W.; Wen, Jiayu; Park, Soo; Suzuki, Ana Maria; Wan, Kenneth H.; Yu, Charles; et al. (Nature (London), 2014)
Animal transcriptomes are dynamic, with each cell type, tissue and organ system expressing an ensemble of transcript isoforms that give rise to substantial diversity. Here we have identified new genes, transcripts and proteins using poly(A) + RNA sequencing from Drosophila melanogaster in cultured cell lines, dissected organ systems and under environmental perturbations. We found that a small set of mostly neural-specific genes has the potential to encode thousands of transcripts each through extensive alternative promoter usage and RNA splicing. The magnitudes of splicing changes are larger between tissues than between developmental stages, and most sex-specific splicing is gonad-specific. Gonads express hundreds of previously unknown coding and long non-coding RNAs (lncRNAs), some of which are antisense to protein-coding genes and produce short regulatory RNAs. Furthermore, previously identified pervasive intergenic transcription occurs primarily within newly identified introns. The fly transcriptome is substantially more complex than previously recognized, with this complexity arising from combinatorial usage of promoters, splice sites and polyadenylation sites. A large-scale transcriptome analysis in Drosophila melanogaster , across tissues, cell types and conditions, provides insights into global patterns and diversity of transcription initiation, splicing, polyadenylation and non-coding RNA expression.